God Helps Those Who Help Themselves: How Recipients’ Efforts Perception Affects Donation - Jin, Fei; Zheng, Zhengyu; Wu, Banggang (Frontiers in Psychology, 2021)
This research examines how recipients’ efforts to get out of the plight affect the empathy they evoke and the subsequent help they receive from donors. Through three experiments, we find that the higher the efforts made by the recipients to get out of the plight, the stronger the donors’ willingness to donate. This effect is moderated by the need severity of the recipients. The more serious the plight is, the stronger the impact of the degree of efforts on the willingness to donate. This research makes theoretical contributions to charitable giving and provides implications for nonprofit organizations on describing recipients’ efforts to get out of their plight.